(untitled) (Research, Society and Development, 2022)
This article aims to highlight the importance of building/using the State of the Art and State of Knowledge method for the development of academic-scientific research. In particular, it presents part of the State of Knowledge on Learning in Higher Education developed for a doctoral research that addresses this theme. This study is qualitative in nature, with a literature review, with a description of the experience lived by the researcher who used twenty-five references, among articles, theses and dissertations (from 2012 to 2022) to carry out the mapping. Regarding the difficulties encountered, it is mentioned: a) few productions that fully contemplated the research theme; b) the absence of information in abstracts; c) the inconsistency of descriptors in the research related to those provided by the authors of the works with the proposed themes; and, finally, d) the difficulty in handling some digital databases. With this study, we came to the conclusion of the importance of differentiating the State of the Art and the State of knowledge, which can be considered thermometers and a fundamental resource for the development and validation of science and that publications on the subject are still very restricted. Still in this opportunity, the research proposes an organizing framework as a tool for the construction of the State of Knowledge, allowing researchers interested in using this method all the benefits pointed out in the course of the text.